2017
DOI: 10.1002/jcp.26210
|View full text |Cite
|
Sign up to set email alerts
|

C‐C motif chemokine ligand 23 abolishes ER stress‐ and LPS‐induced reduction in proliferation of bovine endometrial epithelial cells

Abstract: To reduce embryonic losses in domestic animals for economic production of livestock meat and milk, chemokines and their receptors are required for proper implantation and placentation during early pregnancy. In this study, we investigated the effects of C-C-motif chemokine ligand 23 (CCL23) on the proliferation of bovine endometrial (BEND) epithelial cells. CCL23 treatment improved BEND cell proliferation by enhancing PCNA and cyclin D1 expression via activation of the PI3K/AKT and MAPK signaling pathways. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A bovine endometrial cell model showed that tunicamycin (an antibiotic)-induced ER stress inhibits epithelial cell proliferation ( 72 ). Addition of CCL23 rescued cell proliferation by activating PI3K/AKT and MAPK signaling while simultaneously reducing the expression levels of UPR-signaling proteins, including PERK, IRE1α, and ATF6.…”
Section: Ccl23-directed Er Stress Mitigationmentioning
confidence: 99%
“…A bovine endometrial cell model showed that tunicamycin (an antibiotic)-induced ER stress inhibits epithelial cell proliferation ( 72 ). Addition of CCL23 rescued cell proliferation by activating PI3K/AKT and MAPK signaling while simultaneously reducing the expression levels of UPR-signaling proteins, including PERK, IRE1α, and ATF6.…”
Section: Ccl23-directed Er Stress Mitigationmentioning
confidence: 99%
“…In addition, a strong relationship between UPR and mTOR‐mediated autophagy has been reported in the literature (Gan et al, ; Rui, Xu, Chen, & Zhang, ). In addition, there is a growing number of reports of ER stress‐induced UPR and autophagy involved in female reproduction (Lim, Bae, Bazer, & Song, ; , ; Sobolewska et al, ; Tsukamoto et al, ). The results of this study indicate that COPS5 negatively regulates the ERN1 pathway and is positively correlated with the activity of mTOR‐autophagy signaling in this model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCL23 promotes the vascular endothelial growth factor (VEGF)-induced propagation and migration of endothelial cells [ 13 ]. Furthermore, CCL23 eliminates the endoplasmic reticulum stress and lipopolysaccharide-induced proliferation reduction in bovine endometrial epithelial cells [ 14 ]. In contrast, there are currently few studies indicating the involvement of CCL23 in cancer.…”
Section: Introductionmentioning
confidence: 99%